The Relation Between Epicardial Fat Tissue Thickness and TSH Receptor Antibody in Hyperthyroidism - Altunbaş, Rıza; Eren, Mehmet Ali; Altıparmak, İbrahim Halil; Karaaslan, Hüseyin; Sabuncu, Tevfik (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Although hyperthyroidism may be associated with atherosclerosis, its pathogenesis is not well known. TSH receptor antibody (TRAb) has been shown to be responsible for increased orbital fat tissue in Graves ophthalmopathy. Epicardial fat tissue thickness (EFT) has been found to be increased in case of overt hyperthyroidism. In our study, we aimed to investigate if TRAb is associated with the increased EFT in newly diagnosed hyperthyroidism.Methods Twenty six TRAb positive (group 1) and 26 TRAb negative (group 2) newly diagnosed patients with hyperthyroidism, and 26 healthy control subjects (group 3) were enrolled. EFT was measured by the same cardiologist using an echocardiography device. Serum TRAb levels were measured by the radio-receptor assay and levels above 1.75 IU/L were considered as positive.Results There was no difference among groups in terms of age, gender and body mass index. Although there was no significant difference between group 1 and 2, both group 1 (0.38±0.15 cm) and group 2 (0.4±0.17 cm) had significantly higher EFT levels when compared to group 3 (0.25±0.06 cm) (p=0.004 and p=0.001, respectively). However we did not find any correlation between TRAb and EFT levels.Conclusion The results of our study suggested that EFT was increased in hyperthyroidism and this increasing was not dependent of TRAb level. EFT elevation might be depending directly to the cardiovascular effects of hyperthyroidism.
Keywords: hyperthyroidism; TSH receptor antibody; epicardial fat tissue thickness